Uptake and use of gender research approaches and tools from the project “GENNOVATE” by agriculture researchers worldwide - CGIAR Research Program on Maize (2018)
GENNOVATE is a global comparative research initiative across 11 CGIAR Research Programs that addresses the question of how gender norms and agency influence men, women, and youth to adopt innovation in agriculture and natural resource management. Findings from this work are being taken up by international and national agricultural researchers and impacting how they how they target, plan and realize their research work to better reach men, women and youth.